LENGTH-WEIGHT RELATIONSHIP IN THE SNAPPER, LUTIANUS KASMIRA (FORSKAh) - Rengarajan, K (Indian Journal of Fisheries, 2011)
The length-weight relationship in Lutianus kasmira has been worked out ffoih samples collected at Fori BMr, "Andamans during the years-t966"68. The value of the exponent ’o’ in the parabolic equation was found to be very nearly 3.0. The relation between length and weight in this species could be expressed by the hypothetical cube law. The observed and calculated weights for the corresponding lengths showed a close relationship. No significant variation in the regression coefficfent was noticed between the two sexes or betweeir the years.^